Efecto de la roca fosfórica como enmienda en el manejo de suelos ácidos - Valenzuela Barre, Patricio Alexander (2024)
The present work compiled information regarding the effects caused by phosphate rock as an amendment in acidic soils. This amendment is a natural mineral rich in phosphorus, it plays a fundamental role in agriculture by improving soil fertility and promoting plant growth. The objective of the research determined the positive and negative effects and the dose of phosphate rock for direct application to the soil. Taking into account that its application as a fertilizer supplies phosphorus, essential for processes such as root development, flower and seed formation, and energy storage. The methodology proposed to carry out this research in a timely manner was based on updated bibliographic documents, taking into account their veracity. Research on the use of rock phosphate in agriculture is crucial to develop sustainable alternatives, improve soil productivity and promote environmentally friendly agricultural practices. The results indicate that when using this amendment there is a better availability of other nutrients in the soil and efficient stimulation of root development. The conclusions presented based on the analysis of the reviewed information determined that this compound especially benefits acidic soils by correcting acidity and improving crop production. Before applying phosphate rock, it is crucial to perform a detailed soil analysis to understand its properties, acidity levels, and specific needs. This will allow a more precise and effective application and in the same way enhance its benefits.